MEMBINGKAI KEBIJAKAN PSBB: ANTARA KEBEBASAN PERS DAN KONTROL PEMERINTAH - Anggraeni, Diana; Qonita, Naila; Nabila, Nabila (Istek Widuri Jakarta, 2023)
This study investigates the approach adopted by Kompas.com to navigate the delicate balance between press freedom and government control in Indonesia. Employing a qualitative methodology based on framing analysis components developed by Robert N. Entman, the research scrutinizes 237 news stories featured on the Kompas.com portal, identifying discernible patterns. Utilizing Entman's framing analysis, the study seeks to comprehend how Kompas.com conveys information about the PSBB (Large-Scale Social Restrictions) and presents potential solutions to this issue. The analysis reveals that the Government is prominently featured as the primary news source in 83.05% of cases, encompassing 197 news stories, while NGOs (1.265%), experts (7.59%), and communities (8.01%) are introduced to provide limited alternative perspectives. Kompas.com tends to employ a positive framing approach, skillfully balancing the delivery of accurate information, endorsement of government policies, and avoidance of potential conflicts. The exercise of press freedom, shaped by considerations of political and social factors, reflects the intricate nature of the media-government relationship in Indonesia.